Economic prospects of ocean iron fertilization in an international carbon market - Wilfried Rickels; Katrin Rehdanz; Andreas Oschlies (Kiel Institute for the World Economy (IfW), 2009)
To stay within the 2êC temperature increase target for climate change calls for ambitious emission reduction targets already for the 2012-2020 compliance period. Cost-efficiency is a crucial criterion for the enforcement of such ambitious targets, requiring analyses of all possible abatement options. Among others, enhancing the oceanic carbon sink by ocean iron fertilization (OIF) could be such an option. In our analysis we consider short-term large-scale OIF modeling experiments for a Post-Kyoto compliance problem to assess the economic prospects of OIF. Our analysis reveals that the critical unit costs per net ton of CO2 sequestered by OIF are in a range of 22 to 28 USD (price level 2000) assuming that the current limitations regarding the use of carbon credits generated in low cost countries and from forestation is completely relaxed. The critical unit costs are determined as those that would make an emitter indifferent between various abatement options. We are also able to show that already seven years of OIF in the area of 30ê south provide the same amount of credits equivalent to a global forestation project for the duration of 20 years. Over all and from economic perspective, our results indicate that OIF can be considered as an additional abatement option, but, further research, especially on adverse side effects, is needed.
Keywords: Q52; Q54; 330; Climate change; sink enhancement; ocean iron fertilization; CO2 market; emission trading; Klimaschutz; Meer; Düngemittel; Stahl; Kosten-Nutzen-Analyse; Emissionsrechte; Emissionshandel; Welt